Selective Glucocorticoid Receptor (GR-II) Antagonist Reduces Body Weight Gain in Mice - Tomoko Asagami; Joseph K. Belanoff; Junya Azuma; Christine M. Blasey; Robin D. Clark; Philip S. Tsao (Journal of Nutrition and Metabolism)
Previous research has shown that mifepristone can prevent and reverse weight gain in animals and human subjects taking antipsychotic medications. This proof-of-concept study tested whether a more potent and selective glucocorticoid receptor antagonist could block dietary-induced weight gain and increase insulin sensitivity in mice. Ten-week-old, male, C57BL/6J mice were fed a diet containing 60% fat calories and water supplemented with 11% sucrose for 4 weeks. Groups (𝑛=8) received one of the following: CORT 108297 (80 mg/kg QD), CORT 108297 (40 mg/kg BID), mifepristone (30 mg/kg BID), rosiglitazone (10 mg/kg QD), or vehicle. Compared to mice receiving a high-fat, high-sugar diet plus vehicle, mice receiving a high-fat, high-sugar diet plus either mifepristone or CORT 108297 gained significantly less weight. At the end of the four week treatment period, mice receiving CORT 108297 40 mg/kg BID or CORT 108297 80 mg/kg QD also had significantly lower steady plasma glucose than mice receiving vehicle. However, steady state plasma glucose after treatment was not highly correlated with reduced weight gain, suggesting that the effect of the glucocorticoid receptor antagonist on insulin sensitivity may be independent of its mitigating effect on weight gain.